Simmondsins quantification by spectrophotometry UV–vis in press cake and in jojoba seeds (Simmondsia chinensis (Link) Schneider), from Argentina - Gayol, Maria Fernanda (2008)
In this paper, we describe a simple, fast, and efficient method for the quantification of simmondsins and simmondsin's ferulates in jojoba seeds and residual cakes, without using expensive equipment or laborious techniques. Spectrophotometric measurements (UV–vis) were used for the quantification of the content of simmondsins, total ferulates and total simmondsins in jojoba seeds and residual cakes from the provinces of Catamarca and La Rioja, Argentina. The average values of such components found in seeds, in 100 g of dry and defatted sample, were 11.54 ± 0.91 and 2.24 ± 0.28 g of simmondsins and of simmondsin's ferulates, respectively, whereas the respective values in residual cakes were 10.08 ± 0.31 and 2.93 ± 0.64 g, respectively. A great diversity between the simmondsin contents and their ferulates in seed samples of different origins as well as in different clones was observed. The residual cakes did not present differences respect to the simmondsin contents; however, there were some difference with the simmondsin ferulates. These variations are due to the genetic antecedents of plants and the environmental conditions in which they grow.